REPRESENTASI TRI HITA KARANA DALAM SESAJI PUJAN KASANGA TENGGER: KAJIAN KOSMO-GASTRONOMI SASTRA: Indonesia - Tsabitah Zain Mumtaz; Darni; Resdianto Permata Raharjo; Anas Ahmadi; Moh. Ahsan Shohifur Rizal (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
The Pujan Kasanga ritual is a cultural heritage of the Tengger community that is rich in food symbolism and theological values. This study focuses on strengthening the meaning of cosmo-gastronomic constructions in Pujan Kasanga offerings through the perspective of Tri Hita Karana and their relevance to the Sustainable Development Goals (SDGs). The research employed a qualitative method with an ethnographic approach. Data were collected through participant observation and in-depth interviews with key informants in Ngadiwono, Tosari, and Mororejo Villages. The data analysis process was conducted through stages of data reduction, data presentation, and conclusion drawing based on the theory of cultural symbolism. The findings reveal that the Juadah Merah-Putih offering and Ayam Pancawarna represent spiritual manifestations (Parahyangan) that support cultural preservation in line with SDG 11. The use of Juadah Kirik and Pasung-Pepes symbolizes the management of social harmony and gender equality (Pawongan), which aligns with SDG 16 and SDG 5. The utilization of local white corn, Tamping, and Beboreh reflects food sovereignty and ecological ethics (Palemahan), corresponding with SDG 2 and SDG 15. This study concludes that Pujan Kasanga functions as a visionary social technology in harmonizing spirituality, social stability, and environmental sustainability to achieve sustainable development.